EMU and European government bond market integration - Abad, Pilar; Chuliá, Helena; Gómez-Puig, Marta (Journal of Banking & Finance, 2010)
In this study we adopt the CAPM-based model of Bekaert and Harvey (1995) to compare the differences in the relative importance of two sources of systemic risk (world and Eurozone) on Government bond returns, in two groups of countries in EU-15. Results show that euro markets are less vulnerable to the influence of world risk factors, and more vulnerable to EMU risk factors. However, they are only partially integrated. For their part, the markets of the countries that decided to stay out of the Monetary Union present a higher vulnerability to external risk factors.